Heavy metal remover for industrial wastewater and preparation method of heavy metal remover

Magnetic porous materials are formed by polymerizing ceramic particles and iron ion loading, silane coupling agent bridges and monomers, which solves the problem of poor removal of high-concentration heavy metal wastewater in the prior art, and achieves efficient removal and good stability Heavy metal remover.

CN119215869APending Publication Date: 2024-12-31JIANGSU JIANLIN ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411391646.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove industrial wastewater containing high concentrations of heavy metals, and the removal effect of ordinary water treatment agents is not ideal in this case.

Method used

Ceramic particles are used as the matrix material, and magnetic porous materials are formed by calcining, impregnation, iron ions supported, silane coupling agent bridges and monomer polymerization, thereby improving adsorption and dispersion, and forming a semi-covered structure to enhance the removal effect.

Benefits of technology

It realizes efficient removal of high-concentration heavy metals, and is easy to recover through magnetic properties. It also reduces the adsorption effect after multiple uses and has high stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a heavy metal remover in industrial wastewater and a preparation method thereof.The preparation method comprises the steps that ceramic particles and tetrabutyl titanate are mixed and calcined, then the mixture is soaked in a ferric salt solution, and magnetic ceramic particles are obtained through oxidation; and mixing with hydroxyethyl cellulose, and dropwise adding a monomer for polymerization. According to the invention, ceramic particles are used as a base material, a porous material containing TiO2 and having oxygen vacancies is firstly prepared, the porous material has strong adsorbability and photocatalysis and can effectively adsorb heavy metal ions in water, iron ions are loaded in the porous material, and ferroferric oxide formed after oxidation has magnetism, so that the magnetic ceramic particles are easy to recover; then connecting with hydroxyethyl cellulose under the bridging action of KH550, so as to improve the dispersity and flocculability of the material and further assist in improving the removal effect of the material on heavy metal ions; meanwhile, hydrophilic and lipophilic monomers are polymerized and self-assembled in situ on the surface, so that semi-coating is formed on the surfaces of ceramic particles, the stability of the material is improved, and the cyclic utilization rate is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water treatment, in particular to a heavy metal remover in industrial wastewater and a preparation method thereof. Background Art

[0002] With the rapid development of industrialization, water pollution has become increasingly serious. Heavy metal pollution in water bodies often occurs in industries such as metal electroplating, metallurgy, mining, and fossil fuels. Common heavy metals include mercury, lead, zinc, copper, nickel, chromium, etc., which are enriched and difficult to degrade. Heavy metals can enter the human body through bioaccumulation and endanger human health and safety. Therefore, the removal of heavy metals in water bodies is particularly important.

[0003] At present, the main methods for wastewater treatment are: physical adsorption, ion exchange, chemical precipitation, microbial treatment, etc. Different treatment methods use different water treatment agents, but there is still a lack of special treatment agents for metal adsorption and removal. Ordinary water treatment agents such as coagulation-flocculants can also effectively adsorb some heavy metal ions, but for wastewater with high heavy metal content, they often cannot achieve the ideal removal effect. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention proposes a treatment agent that can be used to treat industrial wastewater containing relatively high concentrations of heavy metals, which can effectively remove heavy metals in water.

[0005] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a heavy metal remover in industrial wastewater comprises the following steps: S1: dispersing ceramic particles in anhydrous ethanol, adding tetrabutyl titanate to mix well, removing the solvent, placing the mixture in a crucible and calcining under a nitrogen atmosphere; S2: The calcined material is immersed in a ferrous sulfate or ferrous chloride solution overnight, then an alkaline solution is added and heated to 60°C for reaction for 2-3 hours, and then filtered and washed to obtain magnetic ceramic particles; S3: Disperse the magnetic ceramic particles in the hydroxyethyl cellulose aqueous solution, add KH550 to the mixture, and heat under reflux in a water bath overnight; S4: under a nitrogen atmosphere, add ammonium persulfate to the mixed solution of step S3 and stir evenly, heat to 70° C., then dropwise add a hydrophilic monomer to react for a certain period of time, then slowly dropwise add a hydrophobic monomer, continue to stir for 1 hour after the dropwise addition is completed, then place the reaction system in an ice water bath to cool, filter, and dry to obtain; The hydrophilic monomer is mercapto polyethylene glycol methacrylate, which is dissolved in water when used; the hydrophobic monomer is one of butyl acrylate, methyl methacrylate and butyl methacrylate, which is dissolved in ethanol aqueous solution with ammonium persulfate when used.

[0006] Furthermore, the mass ratio of the ceramic particles to tetrabutyl titanate is 10:0.2-0.5.

[0007] Furthermore, the calcination conditions in step S1 are as follows: in a nitrogen atmosphere, the temperature is first increased to 300-400°C at a heating rate of 5°C / min, and then the temperature is increased to 600-800°C at a heating rate of 3°C / min after being kept at this temperature for 30 min.

[0008] Furthermore, in step S2, the concentration of the ferrous sulfate or ferrous chloride solution is 1 mol / L; the mass volume ratio of the calcined material to the ferrous sulfate or ferrous chloride solution is 1 g:3~5 mL.

[0009] Furthermore, in step S3, the mass ratio of magnetic ceramic particles, hydroxyethyl cellulose and KH550 is 1:1:0.5.

[0010] Furthermore, the molecular weight of mercapto polyethylene glycol methacrylate is 1000, and the molar ratio of mercapto polyethylene glycol methacrylate to butyl acrylate is 1:2-5.

[0011] The present invention further provides a heavy metal remover in industrial wastewater prepared by the preparation method described above.

[0012] Compared with the prior art, the beneficial effects of the present invention are as follows: in this case, ceramic particles are used as the matrix material, and a porous material containing TiO2 with oxygen vacancies is first prepared, which has strong adsorption and photocatalytic properties and can effectively adsorb heavy metal ions in water. Iron ions are loaded in the porous material, and after oxidation, ferroferric oxide is formed, which has magnetism, making the magnetic ceramic particles easy to recycle; then, the material is connected with hydroxyethyl cellulose under the bridging effect of silane coupling agent KH550 to improve the dispersibility and flocculation of the material, and further help improve the material's removal effect on heavy metal ions; at the same time, hydrophilic and lipophilic monomers are polymerized on its surface, self-assembled in situ, and then semi-coated on the surface of the ceramic particles, thereby improving the stability of the material and having a high recycling rate. DETAILED DESCRIPTION

[0013] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0014] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0015] Example 1: A heavy metal remover S1: 10 parts by weight of ceramic particles are dispersed in anhydrous ethanol, 0.5 parts by weight of tetrabutyl titanate is added to mix them evenly, the solvent is removed, the mixture is placed in a crucible and calcined in a nitrogen atmosphere, firstly heated to 300-400°C at a heating rate of 5°C / min, kept at this temperature for 30 min, and then heated to 600-800°C at a heating rate of 3°C / min; S2: The calcined material was immersed in 1 mol / L ferrous sulfate overnight, with a mass volume ratio of 1g:5mL, and then sodium hydroxide solution was added and heated to 60°C for 2-3h, and filtered and washed to obtain magnetic ceramic particles; S3: Weigh equal masses of magnetic ceramic particles and hydroxyethyl cellulose, dissolve the hydroxyethyl cellulose in water, then disperse the magnetic ceramic particles in the aqueous solution, add 0.5 times the amount of KH550 to the mixed solution, and heat in a water bath and reflux overnight; S4: under a nitrogen atmosphere, add ammonium persulfate to the mixed solution of step S3 and stir evenly, heat to 70° C., then dropwise add a hydrophilic monomer to react for a certain period of time, then slowly dropwise add a hydrophobic monomer, continue to stir for 1 hour after the dropwise addition is completed, then place the reaction system in an ice water bath to cool, filter, and dry to obtain; Among them, the hydrophilic monomer is mercapto polyethylene glycol methacrylate (molecular weight 1000), which is dissolved in water when used; the hydrophobic monomer is butyl acrylate, which is dissolved in ethanol aqueous solution with ammonium persulfate when used; the molar ratio of mercapto polyethylene glycol methacrylate to butyl acrylate is 1:2.

[0016] Example 2: A heavy metal remover S1: 10 parts by weight of ceramic particles are dispersed in anhydrous ethanol, 0.5 parts by weight of tetrabutyl titanate is added to mix them evenly, the solvent is removed, the mixture is placed in a crucible and calcined in a nitrogen atmosphere, firstly heated to 300-400°C at a heating rate of 5°C / min, kept at this temperature for 30 min, and then heated to 600-800°C at a heating rate of 3°C / min; S2: The calcined material was immersed in 1 mol / L ferrous chloride overnight, with a mass volume ratio of 1g:4mL, and then sodium hydroxide solution was added and heated to 60°C for 2-3h, and then filtered and washed to obtain magnetic ceramic particles; S3: Weigh equal masses of magnetic ceramic particles and hydroxyethyl cellulose, dissolve the hydroxyethyl cellulose in water, then disperse the magnetic ceramic particles in the aqueous solution, add 0.5 times the amount of KH550 to the mixed solution, and heat in a water bath and reflux overnight; S4: under a nitrogen atmosphere, add ammonium persulfate to the mixed solution of step S3 and stir evenly, heat to 70° C., then dropwise add a hydrophilic monomer to react for a certain period of time, then slowly dropwise add a hydrophobic monomer, continue to stir for 1 hour after the dropwise addition is completed, then place the reaction system in an ice water bath to cool, filter, and dry to obtain; Among them, the hydrophilic monomer is mercapto polyethylene glycol methacrylate (molecular weight 1000), which is dissolved in water when used; the hydrophobic monomer is butyl acrylate, which is dissolved in ethanol aqueous solution with ammonium persulfate when used; the molar ratio of mercapto polyethylene glycol methacrylate to butyl methacrylate is 1:3.

[0017] Example 3: A heavy metal remover S1: 10 parts by weight of ceramic particles are dispersed in anhydrous ethanol, 0.5 parts by weight of tetrabutyl titanate is added to mix them evenly, the solvent is removed, the mixture is placed in a crucible and calcined in a nitrogen atmosphere, firstly heated to 300-400°C at a heating rate of 5°C / min, kept at this temperature for 30 min, and then heated to 600-800°C at a heating rate of 3°C / min; S2: The calcined material was immersed in 1 mol / L ferrous chloride overnight, with a mass volume ratio of 1g:5mL, and then sodium hydroxide solution was added and heated to 60°C for 2-3h, and filtered and washed to obtain magnetic ceramic particles; S3: Weigh equal masses of magnetic ceramic particles and hydroxyethyl cellulose, dissolve the hydroxyethyl cellulose in water, then disperse the magnetic ceramic particles in the aqueous solution, add 0.5 times the amount of KH550 to the mixed solution, and heat in a water bath and reflux overnight; S4: under a nitrogen atmosphere, add ammonium persulfate to the mixed solution of step S3 and stir evenly, heat to 70° C., then dropwise add a hydrophilic monomer to react for a certain period of time, then slowly dropwise add a hydrophobic monomer, continue to stir for 1 hour after the dropwise addition is completed, then place the reaction system in an ice water bath to cool, filter, and dry to obtain; Among them, the hydrophilic monomer is mercapto polyethylene glycol methacrylate (molecular weight 1000), which is dissolved in water when used; the hydrophobic monomer is butyl acrylate, which is dissolved in ethanol aqueous solution with ammonium persulfate when used; the molar ratio of mercapto polyethylene glycol methacrylate to butyl acrylate is 1:5.

[0018] Comparative Example 1: S1: The ceramic particles were immersed in 1 mol / L ferrous chloride overnight, with a mass volume ratio of 1g:4mL, and then sodium hydroxide solution was added and heated to 60℃ for 2-3h, and then filtered and washed to obtain magnetic ceramic particles; S2: Weigh equal masses of magnetic ceramic particles and hydroxyethyl cellulose, dissolve the hydroxyethyl cellulose in water, then disperse the magnetic ceramic particles in the aqueous solution, add 0.5 times the amount of KH550 to the mixed solution, and heat in a water bath and reflux overnight; S3: under nitrogen atmosphere, add ammonium persulfate to the mixed solution of step S3 and stir evenly, heat to 70° C., then dropwise add hydrophilic monomer to react for a certain time, then slowly dropwise add hydrophobic monomer, continue to stir for 1 hour after the dropwise addition is completed, then cool the reaction system in an ice water bath, filter and dry to obtain; Among them, the hydrophilic monomer is mercapto polyethylene glycol methacrylate (molecular weight 1000), which is dissolved in water when used; the hydrophobic monomer is butyl acrylate, which is dissolved in ethanol aqueous solution with ammonium persulfate when used; the molar ratio of mercapto polyethylene glycol methacrylate to butyl methacrylate is 1:3.

[0019] Comparative Example 2: S1: 10 parts by weight of ceramic particles are dispersed in anhydrous ethanol, 0.5 parts by weight of tetrabutyl titanate is added to mix them evenly, the solvent is removed, the mixture is placed in a crucible and calcined in a nitrogen atmosphere, firstly heated to 300-400°C at a heating rate of 5°C / min, kept at this temperature for 30 min, and then heated to 600-800°C at a heating rate of 3°C / min; S2: The calcined material was immersed in 1 mol / L ferrous chloride overnight, with a mass volume ratio of 1g:4mL, and then sodium hydroxide solution was added and heated to 60°C for 2-3h, and then filtered and washed to obtain magnetic ceramic particles; S3: Weigh equal masses of magnetic ceramic particles and hydroxyethyl cellulose, dissolve the hydroxyethyl cellulose in water, then disperse the magnetic ceramic particles in the aqueous solution, add 0.5 times the amount of KH550 to the mixed solution, heat in a water bath and reflux overnight, filter, wash with water, and dry to obtain the mixture.

[0020] Comparative Example 3: S1: 10 parts by weight of ceramic particles are dispersed in anhydrous ethanol, 0.5 parts by weight of tetrabutyl titanate is added to mix them evenly, the solvent is removed, the mixture is placed in a crucible and calcined in a nitrogen atmosphere, firstly heated to 300-400°C at a heating rate of 5°C / min, kept at this temperature for 30 min, and then heated to 600-800°C at a heating rate of 3°C / min; S2: The calcined material was immersed in 1 mol / L ferrous chloride overnight, with a mass volume ratio of 1g:4mL, and then sodium hydroxide solution was added and heated to 60°C for 2-3h, and then filtered and washed to obtain magnetic ceramic particles; S3: Disperse the magnetic ceramic particles in water, add ammonium persulfate to the dispersion under a nitrogen atmosphere and stir evenly, heat to 70°C, then drop a hydrophilic monomer to react for a certain period of time, then slowly drop a hydrophobic monomer, continue stirring for 1 hour after the dropwise addition is completed, then cool the reaction system in an ice water bath, filter, and dry to obtain; Among them, the hydrophilic monomer is mercapto polyethylene glycol methacrylate (molecular weight 1000), which is dissolved in water when used; the hydrophobic monomer is butyl acrylate, which is dissolved in ethanol aqueous solution with ammonium persulfate when used; the molar ratio of mercapto polyethylene glycol methacrylate to butyl methacrylate is 1:3.

[0021] Experiment: Evaluation of the removal effect of removers on heavy metals in wastewater Simulate industrial wastewater and prepare Cu 2+ 、Zn 2+ 、Cd 2+ Cr 2+ , Pb 2+ , Hg 2+ 、Ni 2+ For samples with 10 mg / L and 50 mg / L contents, take 1L of the sample, add 10 mg of the remover, stir for 1 hour, and then let it stand for 5 hours for adsorption. Calculate the removal rate of each ion, which is recorded as R1; repeat the above steps to adsorb the new sample after magnetic recovery and regeneration. After repeating ten times, calculate the removal rate of the tenth time, which is recorded as R 10 ; Compare the removal effects of the removers of different embodiments and comparative examples on heavy metals in different samples to be tested. The results are shown in Tables 1 and 2.

[0022] Table 1 (10 mg / L sample to be tested) Table 2 (50 mg / L test sample) It can be seen from Table 1 and Table 2 that the removers prepared in Examples 1-3 of the present application have excellent removal effects on both low-concentration and high-concentration metal ion aqueous solutions under the same dosage. And from Table 1, the adsorption removal effect of Examples 1-3 on metal ions decreases very little after ten regenerations, indicating that the magnetic remover has high stability, while from Comparative Example 2, it can be seen that the removal rate after regeneration decreases significantly. Observing Table 2, the average removal rate can still reach more than 98% when treating high-concentration metal ion wastewater with a smaller amount of remover, and the removal rate can be increased by increasing the amount of remover, but at the same dosage, the removal rates of Comparative Examples 1-3 for high-concentration metal ion wastewater have obvious decreases to varying degrees, and the treatment effect is greatly reduced.

[0023] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A method for preparing a heavy metal remover in industrial wastewater, characterized in that: The steps include: S1: dispersing ceramic particles in anhydrous ethanol, adding tetrabutyl titanate to mix well, removing the solvent, placing the mixture in a crucible and calcining under a nitrogen atmosphere; S2: The calcined material is immersed in ferrous sulfate or ferrous chloride solution overnight, then an alkaline solution is added and heated to 60 °C for 2-3 h, filtered and washed to obtain magnetic ceramic particles; S3: Disperse the magnetic ceramic particles in the hydroxyethyl cellulose aqueous solution, add KH550 to the mixture, and heat under reflux in a water bath overnight; S4: under a nitrogen atmosphere, add ammonium persulfate to the mixed solution of step S3 and stir evenly, heat to 70° C., then dropwise add a hydrophilic monomer to react for a certain period of time, then slowly dropwise add a hydrophobic monomer, continue to stir for 1 hour after the dropwise addition is completed, then place the reaction system in an ice water bath to cool, filter, and dry to obtain; The hydrophilic monomer is mercapto polyethylene glycol methacrylate, which is dissolved in water when used; the hydrophobic monomer is one of butyl acrylate, methyl methacrylate and butyl methacrylate, which is dissolved in ethanol aqueous solution with ammonium persulfate when used.

2. The method for preparing a heavy metal remover in industrial wastewater according to claim 1, characterized in that: The mass ratio of the ceramic particles to tetrabutyl titanate is 10:0.2-0.

5.

3. The method for preparing a heavy metal remover in industrial wastewater according to claim 1, characterized in that: The calcination conditions in step S1 are as follows: in a nitrogen atmosphere, the temperature is first increased to 300-400°C at a heating rate of 5°C / min, and then the temperature is increased to 600-800°C at a heating rate of 3°C / min after being kept at this temperature for 30 min.

4. The method for preparing a heavy metal remover in industrial wastewater according to claim 1, characterized in that: In step S2, the concentration of the ferrous sulfate or ferrous chloride solution is 1 mol / L; the mass volume ratio of the calcined material to the ferrous sulfate or ferrous chloride solution is 1 g:3-5 mL.

5. The method for preparing a heavy metal remover in industrial wastewater according to claim 1, characterized in that: In the step S3, the mass ratio of the magnetic ceramic particles, hydroxyethyl cellulose and KH550 is 1:1:0.

5.

6. The method for preparing a heavy metal remover in industrial wastewater according to claim 1, characterized in that: The molecular weight of mercapto polyethylene glycol methacrylate is 1000, and the molar ratio of mercapto polyethylene glycol methacrylate to butyl acrylate is 1:2-5.

7. The heavy metal remover in industrial wastewater obtained by the preparation method according to any one of claims 1 to 6.